2020
DOI: 10.1108/jamr-01-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Do employees' attributes and capabilities matter the intention to become a supply chain manager? Structural model analysis

Abstract: PurposeThis study aims to investigate how the employees' attributes, capabilities, behavioral control and behavioral intentions affect their intention to become a supply chain manager (SCM). The study also investigates how employees' capabilities mediate the relationship between attributes and intention to become SCM.Design/methodology/approachThe purposive sampling frame is employed to collect the data, and multiple statistical tools and techniques are used for analyzing the data.FindingsThe findings reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Until now, such considerations had not been effectively identified and integrated into a single study, prompting this work to fill that gap. However, justifying the use of AHP and SEM models to evaluate the flexibility during the conventional and changing ergonomics is plausible (Al-Hakim and Hassan, 2013;Newaz et al, 2020;Jakhar, 2015Jakhar, , 2017. SEM does not have a limitation on the number of variables.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, such considerations had not been effectively identified and integrated into a single study, prompting this work to fill that gap. However, justifying the use of AHP and SEM models to evaluate the flexibility during the conventional and changing ergonomics is plausible (Al-Hakim and Hassan, 2013;Newaz et al, 2020;Jakhar, 2015Jakhar, , 2017. SEM does not have a limitation on the number of variables.…”
Section: Discussionmentioning
confidence: 99%
“…Human resource capability refers to the stable employment of co-workers, long-term training of multi-skilled workers, wage system based on skill accumulation (experience), internal promotion, employer/employees' relationship, communication and worker motivation (Newaz et al, 2020). In the context of an integrated audit, people are valuable resources for a company where everyone including the management staff are important.…”
Section: Human Resource Capabilitymentioning
confidence: 99%
“…In the context of an integrated audit, people are valuable resources for a company where everyone including the management staff are important. Newaz et al (2020) reported that auditors and auditees play significant roles in an integrated audit management system. The presence of quality auditors could significantly increase the ability to identify the audit process, such as conformity, and result in increasing the value of the management system (Tirkolaee et al, 2020;Kaziliūnas, 2008).…”
Section: Human Resource Capabilitymentioning
confidence: 99%
“…Supply chain management has become one of the crucial factors in ensuring sustainable business and creating a competitive advantage (Rahman and Zailani, 2017; Shukor et al , 2020; Newaz et al , 2020). Malaysia Investment Development Authority (MIDA) reported that the oil and gas business in Malaysia contributes to about 20% of Malaysia’s gross domestic product (GDP) by 2015 and also holding the fourth highest oil reserves and third-highest natural gas reserve in the Asia-Pacific region (Bernama, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The current study focuses on environmental behaviours as one of the main aspects of the sustainable supply chain. Barbosa-Póvoa et al (2018) and Newaz et al (2020) proposed comprehensive research frameworks that identify the needs and characteristics of employee engagement and supply chain management. It is imperative to determine the enablers of engagement in environmental behaviours in energy-related sectors such as the oil and gas as an environment is an essential element in the oil and gas industry.…”
Section: Introductionmentioning
confidence: 99%